Seed priming improves endosperm weakening, germination, and subsequent seedling development of Solanum lycocarpum St. Hil. - Anese, S.; Silva, Edvaldo Aparecido Amaral da [UNESP][; Davide, A. C.; Rocha Faria, J. M.; Soares, G. C. M.; Matos, A. C. B.; Toorop, P. E. (Ista-int Seed Testing Assoc, 2011)
Seed priming is a treatment to improve seed quality and plant growth upon germination and is applied widely to crop species to improve uniformity and yield. The present study aimed to establish a priming protocol for Solanum lycocarpum St.Hil., to improve germination of the dormant seeds and seedling development for in situ restoration, and to determine the mechanism underlying priming. Priming for 15 d at 15 degrees C in water delivered the optimal priming effect, resulting in the fastest and most uniform germination and a high final germination percentage compared with shorter treatments, higher temperatures and lower water potentials. Seedling development following priming was significantly improved. To determine the role of endosperm weakening during priming, the force required to puncture the endosperm and endo-B-mannanase activity were determined during priming and subsequent germination. Mechanical weakening of the endosperm and development of endo-B-mannanase activity appeared to contribute to the priming effect. Despite the difference in dormancy the mechanism behind priming is similar to that in tomato. Seedling production of S. lycocarpum, e.g. for in situ restoration, would benefit from priming.